Hip fractures in institutionalized elderly people: incidence rates and excess mortality. - Rapp, K; Becker, C; Lamb, S; Icks, A; Klenk, J (2008)
It is assumed that nursing homes are the setting with the highest incidence of hip fractures. This observation is, however, based on very little data. The aim of this study was to analyze hip fracture rates and the associated excess mortality in a large nursing home population. A cohort of >69,000 women and men newly admitted to German nursing homes were used to calculate sex- and age-specific incidence rates of hip fractures. To calculate excess mortality, a retrospective cohort study was conducted. To each patient with a hip fracture (n = 4342), four residents without hip fracture (n = 17,368) were matched by sex, age, and level of care (measure for the need of care). Hazard regression models were applied. During 91,850 person-years, 4342 hip fractures were observed. The crude incidence rates for hip fractures were 50.8/1000 person-years in women and 32.7/1000 person-years in men. The incidence rates increased with increasing age categories and were highest in the first months after admission to the nursing home. Increasing care need reduced the risk of hip fracture. Mortality in patients with a hip fracture was increased (women: hazard rate ratio for the first 3 mo after fracture, 1.72; 95% CI, 1.59-1.86; men: hazard ratio, 2.14; 95% CI, 1.80-2.53), but excess mortality was limited to the first months after injury. Data are presented for hip fracture rates and excess mortality after a hip fracture. Our results have implications on the timing and the allocation of specific measures for hip fracture prevention.